Evidence for generation of unstable suprathermal electron population in the auroral F region. Issue 2 (23rd January 2015) - Akbari, H.; Semeter, J. L.; Hirsch, M. A.; Guio, P.; Nicolls, M. J.
Abstract: Anomalous incoherent scatter radar (ISR) spectra confined to narrow altitude ranges near the F region peak and correlated with dynamic auroral precipitation have previously been identified and explained in terms of the cavitating beam‐driven Langmuir turbulence. In this work we used a one‐dimensional Zakharov simulation to constrain the range of physical mechanisms underlying these observational features. We find that although Langmuir wave collapse and caviton formation generated by electron beams with energies of 1 keV can give rise to similar radar echoes, the predicted spectral features and intensities of such echoes are inconsistent with experimental data acquired by various ISRs. Our results suggest that the free energy for the turbulence must be provided by unstable low‐energy (5 − 20 eV) electron populations and that such populations must be produced locally in the F region ionosphere. Key Points: Ionospheric Langmuir turbulence is generated by suprathermal electrons The suprathermal electrons are generated locally in the ionosphere The generation mechanism for the electrons is not yet understood